Prevalence of Esophageal Motility Disorders Among Patients Presenting with Dysphagia - Zrar Hussein Rasul; Mohammed Omer Mohammed; Abdulla, Blund Sirwan (Zanco Journal of Pure and Applied Sciences, 2026)
Esophageal motility disorders impair normal peristalsis of the esophagus and often lead to dysphagia and represent a clinically significant problem with increasing recognition worldwide. These disorders are commonly encountered in patients presenting with esophageal symptoms, yet their true prevalence remains underreported, particularly in regions where diagnostic facilities are limited including Erbil, Kurdistan region-Iraq. Understanding their burden is essential for improving diagnostic accuracy and patient outcomes. The study aims to clarify the prevalence of oesophagal motility disorders among participants with dysphagia and to study the sensitivity of the diagnostic methods. Additionally, to illustrate demographic, clinical, lifestyle, and psychosocial characteristics of esophageal dysmotility (ED) patients with confirmed esophageal motility disorders. A case-series study was conducted from June 2024 to June 2025 at the Hawler Center for Gastroenterology and Hepatology. A total of 113 adult participants with dysphagia underwent a standardized diagnostic workup including esophageal gastroduodenoscopy (EGD), barium swallow and manometry. Participants with confirmed esophageal motility disorders on manometry were classified as a patient group, while participants without motility disorders served as controls. Data on demographics, medical history, clinical symptoms, lifestyle habits, and psychosocial impact were collected via structured questionnaires. Among participants with dysphagia (113), manometry identified oesophagal motility disorders in 67 (59.3%) of cases, with 22 EGJ outflow obstruction (19.46%) and 21 achalasia (18.58%) being the most common findings. Regurgitation (n=47, 70.15%), vomiting (n=45, 67.16%), and weight loss (n=51, 76.11%) were significantly more prevalent in ED group compared to controls. Alcohol use was lower in ED group, while smoking and hot drink intake were similar. Psychosocial burden, including emotional distress (n=47), impaired quality of life (n=49), and altered eating behaviors (n=34), was significantly greater (p-value <0.0001) in ED group. More than half of ED patients presented with dysphagia are manifested in esophageal dysmotility. Manometry being the gold standard in diagnosis of this group. Lifestyles were more prevalent in such patients. Dysphagia due to motility disorders is associated with older age, specific gastrointestinal symptoms, and a significant psychosocial impact.